Pupillary Dynamics Reveal Computational Cost in Sentence Planning - Sevilla, Yamila Alejandra (2014)
This study investigated the computational cost associated with grammatical planning in sentence production. We measured people's pupillary responses as they produced spoken descriptions of depicted events. We manipulated the syntactic structure of the target by training subjects to use different types of sentences following a colour cue. The results showed higher increase in pupil size for the production of passive and object dislocated sentences than for active canonical subject–verb–object sentences, indicating that more cognitive effort is associated with more complex noncanonical thematic order. We also manipulated the time at which the cue that triggered structure-building processes was presented. Differential increase in pupil diameter for more complex sentences was shown to rise earlier as the colour cue was presented earlier, suggesting that the observed pupillary changes are due to differential demands in relatively independent structure-building processes during grammatical planning. Task-evoked pupillary responses provide a reliable measure to study the cognitive processes involved in sentence production.